Firestarter - King, Stephen, 1947- (New York : Signet, 1981)
Charlie, an eight-year-old girl, has the ability to start fires by pyrokinesis. Now a government agency is after her and wants to use her as a weapon.
Notable/Best Books (A.L.A.).
School Library Journal.
Wilson's Fiction.
Adult
Keywords: Children -- Fiction; Fires -- Fiction; Parapsychology -- Fiction; Children -- Fiction; Fires -- Fiction; Horror fiction; Parapsychology -- Fiction